Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
So,
Let's eliminate the y's.
Multiply the first equation by 2
4x - 6y = 62
Multiply the second equation by 3
9x + 6y = 3
Add the two equations together
13x = 65
Divide both sides by 13
x = 5
Substitute in the second equation
3(5) + 2y = 1
15 + 2y = 1
Subtract 15 from both sides
2y = -14
Divide both sides by 2
y = -7
Check
3(5) + 2(-7) = 1
15 + -14 = 1
1 = 1 This checks.
2(5) - 3(-7) = 31
10 - -21 = 31
10 + 21 = 31
31 = 31 This also checks.
S = {(5,-7)}
Let's eliminate the y's.
Multiply the first equation by 2
4x - 6y = 62
Multiply the second equation by 3
9x + 6y = 3
Add the two equations together
13x = 65
Divide both sides by 13
x = 5
Substitute in the second equation
3(5) + 2y = 1
15 + 2y = 1
Subtract 15 from both sides
2y = -14
Divide both sides by 2
y = -7
Check
3(5) + 2(-7) = 1
15 + -14 = 1
1 = 1 This checks.
2(5) - 3(-7) = 31
10 - -21 = 31
10 + 21 = 31
31 = 31 This also checks.
S = {(5,-7)}
2x - 3y = 31 ⇒ 6x - 9y = 93
3x + 2y = 1 ⇒ 6x + 4y = 2
-5y = 91
-5 -5
y = -18 1/5
2x - 3(-18 1/5) = 31
2x + 54 3/5 = 31
- 54 3/5 - 54 3/5
2x = -24 3/5
2 2
x = -12 3/10
(x, y) = (-12 3/10, -18 1/5)
3x + 2y = 1 ⇒ 6x + 4y = 2
-5y = 91
-5 -5
y = -18 1/5
2x - 3(-18 1/5) = 31
2x + 54 3/5 = 31
- 54 3/5 - 54 3/5
2x = -24 3/5
2 2
x = -12 3/10
(x, y) = (-12 3/10, -18 1/5)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.